ASSESSING THE IMPACT OF VIRTUAL PLATFORMS ON DIGITAL LEXICAL DEVELOPMENT: A CRITICAL ACADEMIC REVIEW - BERDIKULOVA MUNIRA AZIZOVNA, (TADQIQOTLAR, 2026)
ABSTRACT:  This  paper  evaluates  how  web-based  digital  environments influence  vocabulary  mastery  and  long-term  memory  encoding  among  non-native language  learners  (EFL/ESL).  By  analyzing  current  trends  in  computer-assisted pedagogy, the study examines the real-world utility of gamified software, algorithmic spaced-repetition cards, and immersive web portals. The analysis indicates that multi-sensory  online  tasks  significantly  improve  semantic  mapping  and  lower communicative anxiety compared to traditional textbook drills. However, the study also highlights important pedagogical concerns, such as student cognitive fatigue, the brief  lifespan  of  tech-driven  motivation,  and  the  persistent  gap  between  word recognition  and  active  conversational  use.  Finally,  the  author  offers  practical frameworks for combining online learning with active classroom communication.